Distribution of organochlorine pesticides residues in Solanum macrocarpum and Lactuca sativa Cultivated in South of Benin (Cotonou and Seme-Kpodji). - Agnandji, Prudence; AYI-FANOU, Lucie; GBAGUIDI, AMN; CACHON, FB; HOUNHA, M; AGASSOUNON DJIKPO TCHIBOZO, Micheline (My University, 2018)
Organochlorines pesticides (OCPs) which utilization is banned, affect nutrition quality of vegetables. Recent research shown their presence in different vegetables. Since last study carried out in 2007 about vegetables contamination by OCPs residues in Benin, none research is done about OCPs residues monitoring in vegetables. This study was conducted to monitor OCPs residues in two vegetables (Solanum macrocarpum L. and Lactuca sativa L.) collected from 4 farms sites in two communes (Cotonou and Seme-kpodji) of Benin. A total of 31 samples of Solanum macrocarpum L. and Lactuca sativa L. were collected from the study areas and analyzed for 13 OCPs residues, which can be grouped into DDTs, Aldrins, Endosulfans, HCHs and Methoxychlor. The data revealed that 100% of the vegetable samples were contaminated by OCPs residues. Aldrin, Dieldrin, Endrin, Endosulfan sulfate, pp’-DDE and pp’-DDT concentrations found were below the maximum residue limits (MRLs) set by European Union (EU) whereas 31.25%, 37.5%, 43.75% of β-HCH, α-Endosulfan, β-Endosulfan concentrations found in Solanum macrocarpum L. were above the EU MRLs adopted values. In Lactuca sativa L., the levels of β-HCH and β-Endosulfan were about 6.67% each and were above the EU (MRLs). Many of OCPs residues levels are below MRLs while three OCPs residues exceeded EU MLRs. This observation suggests that vegetables contamination is due to the persistence of OCPs residues in the soil where vegetables were cultivated. We therefore propose the monitoring of OCPs and other pesticide residues in vegetables cultivated in Benin to perform nutritional quality of vegetables.
Keywords: vegetables; organochlorine pesticides; Benin; health; environment